Enhanced electrical conductivity into PA6 thermoelectric fabric modified by PEDOT-Tosylate for efficient heat harvesting. (January 2023) - Shang, Jichao; Zhao, Xiaofang; Zhang, Jingguang; Liu, Haihui; Zhang, Xingxiang
Abstract: Thermoelectric (TE) fabric can be seamlessly integrated into garments to power portable electronic devices by harvesting body heat. Hence, a flexible PEDOT-Tos/PDA/PA6 thermoelectric fabric was successfully prepared by depositing polydopamine (PDA) on polyamide 6 (PA6) fabric and exploiting the interaction between PDA and PEDOT-Tosylate (PEDOT-Tos). The resistance of TE fabric was only 10.56 Ω/□, which was superior to most of the reported PA6 composite fabrics. Finally, a wearable flexible TE device was prepared by using PEDOT-Tos/PDA/PA6 fabrics. When worn on the arm, it can generate an output voltage of 2.4 mV, which indicated that the TE fabric had a potential application in wearable energy harvesting devices. Graphical abstract: Image 1 Highlights: The highly conductive and low-cost TE fabric by depositing PDA into PEDOT-Tos/PA6 fabric. The introduction of PDA provides TE fabric with excellent stability and adaptability. A six-leg f-TEG based on PEDOT-Tos/PDA/PA6 fabric produces 2.4 mV output voltage (ΔT ≈ 10 K). The TE fabric has the potential for industrial production.